The Role of Religiosity in Moderating the Decision To Use Sharia-Compliant Insurance Services - Efendi, Yola Puspita; Wijayanti, Anita (Universitas Airlangga, 2025)
This quantitative correlational study analyzes factors influencing millennial generation decisions to use Islamic insurance, considering religiosity's moderating effect. The study investigates Islamic financial literacy, risk perception, and trust in Islamic financial institutions roles in shaping such decisions. Data from 116 Indonesian millennials were analyzed using Partial Least Squares – Structural Equation Modeling (PLS-SEM). Findings show that Islamic financial literacy, risk perception, and trust in Islamic financial institutions have positive and significant effects on Islamc insurance usage decisions. Religiosity does not significantly moderate the effects of Islamic financial literacy and risk perception on decisions, but moderates the relationship between trust in Islamic financial institutions and decisions at ten percent significance level. Results highlight the importance for Islamic insurance providers to enhance financial literacy and build trust as key strategies to attract millennial customers. This study contributes to Extended Theory of Planned Behavior application by clarifying religiosity's role in Islamic-based financial decisions, reinforcing Theory of Planned Behavior validity, and enriching Risk Perception Theory and Trust Theory in explaining consumer behavior in Islamic finance context.